NDVI Sensibility to Rainfall Spatial Distribution in ADJOHOUN (Benin, West Africa) (International Journal of Current Engineering and Technology, 2015)
Linear regression analysis confirms a strong sensitivity between East NDVI and East-Center rainfall in Adjohoun with a threshold of 0.54%. Indeed, the reduction in 1236.25 units of rain in Central East induced decrease of one unit of East NDVI. Similarly, in the threshold of the 0.1%, there is a strong link between East rainfall and East-Center NDVI and West-Center NDVI. East-Center rain is strongly related to East rain in 0.1% threshold. Indeed, one unit increasing of East rain in the East causes an increase of 4.99 units of NDVI in East-Center and decreasing of 3.8 units of NDVI in East-Center. As for rainfall, increasing of one unit of rain in the East causes increased 0.38 unit of rain in East-Center.
Keywords: NDVI; Rainfall; Adjohoun; reduction; increasing; decreasing.